Valve-in-valve transcatheter aortic valve replacement versus redo aortic valve replacement: which procedure for which patient?. (2nd December 2022) - Hutt, Erika; Mehra, Nandini; Desai, Milind Y.
ABSTRACT: Introduction: Bioprosthetic aortic valves are increasingly being utilized in a younger population due to improved durability and possibility for future valve-in-valve replacement. This has resulted in a larger population of patients with bioprosthetic aortic valve degeneration requiring re-intervention. Despite no head-to-head comparisons between redo surgical aortic valve replacement (SAVR) and valve-in-valve transcatheter aortic valve replacement (ViV TAVR), observational studies suggest a comparable long-term risk between which led to the incorporation of ViV TAVR to current guidelines. Areas covered: This article summarizes the comparative performance of redo SAVR versus ViV TAVR in patients with bioprosthetic valve dysfunction and provides a guide to better understand which procedure is best for which patient. Expert opinion: With the rising use of TAVR, we will be confronted with more bioprosthetic aortic valve degeneration requiring re-intervention. Based on the available evidence and expert consensus, we propose that patients with bioprosthetic aortic valve degeneration be treated with ViV TAVR if they have a history of radiation heart disease, prohibitive surgical risk, and multiple sternotomies; while patients with small prostheses, history of infective endocarditis, those at high risk for coronary obstruction, and those with need for other cardiac surgery will be managed with redo SAVR.